Self‐Confined Growth of Ultrathin 2D Nonlayered Wide‐Bandgap Semiconductor CuBr Flakes. Issue 36 (24th July 2019) - Gong, Chuanhui; Chu, Junwei; Yin, Chujun; Yan, Chaoyi; Hu, Xiaozong; Qian, Shifeng; Hu, Yin; Hu, Kai; Huang, Jianwen; Wang, Hongbo; Wang, Yang; Wangyang, Peihua; et al.
Abstract: 2D planar structures of nonlayered wide‐bandgap semiconductors enable distinguished electronic properties, desirable short wavelength emission, and facile construction of 2D heterojunction without lattice match. However, the growth of ultrathin 2D nonlayered materials is limited by their strong covalent bonded nature. Herein, the synthesis of ultrathin 2D nonlayered CuBr nanosheets with a thickness of about 0.91 nm and an edge size of 45 µm via a controllable self‐confined chemical vapor deposition method is described. The enhanced spin‐triplet exciton ( Z f, 2.98 eV) luminescence and polarization‐enhanced second‐harmonic generation based on the 2D CuBr flakes demonstrate the potential of short‐wavelength luminescent applications. Solar‐blind and self‐driven ultraviolet (UV) photodetectors based on the as‐synthesized 2D CuBr flakes exhibit a high photoresponsivity of 3.17 A W −1, an external quantum efficiency of 1126%, and a detectivity ( D *) of 1.4 × 10 11 Jones, accompanied by a fast rise time of 32 ms and a decay time of 48 ms. The unique nonlayered structure and novel optical properties of the 2D CuBr flakes, together with their controllable growth, make them a highly promising candidate for future applications in short‐wavelength light‐emitting devices, nonlinear optical devices, and UV photodetectors. Abstract : Ultrathin nonlayered 2D wide‐bandgap CuBr nanoflakes are controllably synthesized by self‐confined chemical vapor deposition, and possess abundant room‐temperature exciton behavior and novel nonlinear optical phenomena. Self‐driven and solar‐blind ultraviolet detectors based on the Ag–CuBr Schottky junction are constructed and display outstanding properties of high photoresponsivity, external quantum efficiency, and detectivity ( D *) with fast response rate.